Evaluation of marginal bone loss of dental implants with internal or external connections and its association with other variables: A systematic review - Medeiros, Rodrigo Antonio de [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Vechiato Filho, Aljomar Jose [UNESP]; Santos, Daniela Micheline dos [UNESP]; Freitas da Silva, Emily Vivianne [UNESP]; Goiato, Marcelo Coelho [UNESP] (Elsevier B.V., 2016)
Statement of problem. Different factors can influence marginal bone loss around dental implants, including the type of internal and external connection between the implant and the abutment. The evidence needed to evaluate these factors is unclear. Purpose. The purpose of this systematic review was to evaluate marginal bone loss by radiographic analysis around dental implants with internal or external connections. Material and methods. A systematic review was conducted following the criteria defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Initially, a population, intervention, comparison, and outcome(s) (PICO) question was defined: does the connection type (internal or external) influence marginal bone loss in patients undergoing implantation? An electronic search of PubMed/MEDLINE and Scopus databases was performed for studies in English language published between January 2000 and December 2014 by 2 independent reviewers, who analyzed the marginal bone loss of dental implants with an internal and/or external connection. Results. From an initial screening yield of 595 references and after considering inclusion and exclusion criteria, 17 articles were selected for this review. Among them, 10 studies compared groups of implants with internal and external connections; 1 study evaluated external connections; and 6 studies analyzed internal connections. A total of 2708 implants were placed in 864 patients. Regarding the connection type, 2347 implants had internal connections, and 361 implants had external connections. Most studies showed lower marginal bone loss values for internal connection implants than for external connection implants. Conclusions. Osseointegrated dental implants with internal connections exhibited lower marginal bone loss than implants with external connections. This finding is mainly the result of the platform switching concept, which is more frequently found in implants with internal connections.